Implicit Affective Rivalry: A Behavioral and fMRI Study Combining Olfactory and Auditory Stimulation - Berthold-Losleben, Mark; Habel, Ute; Brehl, Anne-Kathrin; Freiherr, Jessica; Losleben, Katrin; Schneider, Frank; Amunts, Katrin; Kohn, Nils (Frontiers in Behavioral Neuroscience, 2018)
Aversive odors are highly salient stimuli that serve a protective function. Thus, emotional reactions elicited by negative odors may be hardly influenceable. We aim to elucidate if negative mood induced by negative odors can be modulated automatically by positively valenced stimuli. We included 32 healthy participants (16 men) in an fMRI design combining aversive and neutral olfactory stimuli with positive and neutral auditory stimuli to test the influence of aversive olfactory stimuli on subjective emotional state and brain activation when combined with positive and neutral auditory stimuli. The behavioral results show an interaction of negative olfactory stimuli on ratings of disgust, perceived valence of music and subjective affective state, while positive auditory stimulation did not show this interaction. On a neuronal level, we observed main effects for auditory and olfactory stimulation, which are largely congruent with previous literature. However, the pairing of both stimuli was associated with attenuated brain activity in a set of brain areas (supplementary motor area, temporal pole, superior frontal gyrus) which overlaps with multisensory processing areas and pave the way for automatic emotion regulation. Our behavioral results and the integrated neural patterns provide evidence of predominance of olfaction in processing of affective rivalry from multiple sensory modalities.